DEVELOPING APPRECIATIVE LITERATURE TEXTBOOK BASED ON THEMATIC-INTEGRATIVE THROUGH ACTIVE LEARNING TO IMPROVE UNDERGRADUATE STUDENTS’ APPRECIATIVE CAPABILITY ON POETRY AND DRAMA IN ELEMENTARY TECHER EDUCATION PROGRAM - Endang Sri Markamah; St. Y. Slamet; Rukayah Rukayah; Retno Winarni (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The objectives of this research were: (1) to describe students’ and lecturers’ needs on poetry and drama appreciative textbook, (2) to describe the development of textbook model (3) to find the effectiveness of textbook model 4) to describe textbook dissemination. The type of research used was research and development. Research was done through 4 stages: (1) exploration, (2) model development, (3) model testing, (4) dissemination. Exploration stage used qualitative descriptive approach. Data was collected through in-depth interviews, observation, documentation, and questionnaires. Data analysis technique was interactive analysis model. Model testing was done through experimental research. The results of this research were: (1) the exploration stage showed that the poetry and drama learning textbook used by Elementary Teacher Education Program (ETEP) studentsin Surakarta did not meet the students’ and lecturers’ need, (2) model development stage producedappreciative poetry and drama textbook through preliminary field testing; (3) model testing phase was to test effectiveness of the textbook used t-test non-independent technique.It was obtained tobtainof 23 and ttable(90; 0.05)of 1.67. Thus, tobtained (23)> ttable (1.67) which meant that the hypothesis was accepted (Ho was rejected). In conclusion, the Appreciative Poetry and Drama textbook model was effectively improve students' poetry and drama appreciation skills. Dissemination was done through national seminars, article writing in international journals, as well as the publishing of an Integrative-thematic Textbook of Poetry and Drama Learning with ISBN.